Case Report: Osimertinib Followed by Osimertinib Plus Bevacizumab, Personalized Treatment Strategy for a Lung Cancer Patient With a Novel EGFR Exon 20 Insertion D770_N771insGT and Multiple Brain Metastases - Zhi, Xiaoyu; Luo, Jiancheng; Li, Weiwei; Wang, Jinliang; Wang, Yuying; Cai, Yi; Yan, Xiang (Frontiers in Oncology, 2021)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (EGFR-TKIs) are the standard of care for non–small cell lung cancer (NSCLC) patients with EGFR exon 19 deletion and L858R mutations. However, no EGFR TKI has been approved for NSCLC patients harboring insertion mutations in EGFR exon 20 (EGFRex20ins), a subgroup of uncommon EGFR mutations resistant to first-generation EGFR TKIs. This unmet clinical challenge is further complicated by disease progression due to brain metastases (BMs), which limits the use of EGFR TKIs with low intracranial activity. Osimertinib, a third-generation EGFR TKI with high CNS activity, has demonstrated superior efficacy as a first-line treatment for EGFR-mutant NSCLC with or without BM. The VEGF pathway is a key mediator of cancer metastasis and resistance to EGFR TKIs. Accumulating evidence has demonstrated that the addition of anti-VEGF agents to EGFR TKIs provides an alternative treatment option for the clinical management of EGFR-mutant NSCLC. We herein report an NSCLC case with a novel EGFRex20ins mutation D770_N771insGT and multiple brain metastases who briefly responded to first-line osimertinib treatment and subsequently achieved prolonged disease control with osimertinib plus bevacizumab as second-line treatment. Our case suggests that osimertinib in combination with bevacizumab may be an effective option for NSCLC patients with specific EGFRex20ins mutations and brain metastases.